Unravelling the Roles of Nitrogen Nutrition in Plant Disease Defences - Sun, Yuming (Int J Mol Sci, 2020)
Nitrogen (N) is one of the most important elements that has a central impact on plant growth and yield. N is also widely involved in plant stress responses, but its roles in host-pathogen interactions are complex as each affects the other. In this review, we summarize the relationship between N nutrition and plant disease and stress its importance for both host and pathogen. From the perspective of the pathogen, we describe how N can affect the pathogen’s infection strategy, whether necrotrophic or biotrophic. N can influence the deployment of virulence factors such as type III secretion systems in bacterial pathogen or contribute nutrients such as gamma-aminobutyric acid to the invader. Considering the host, the association between N nutrition and plant defence is considered in terms of physical, biochemical and genetic mechanisms. Generally, N has negative effects on physical defences and the production of anti-microbial phytoalexins but positive effects on defence-related enzymes and proteins to affect local defence as well as systemic resistance. N nutrition can also influence defence via amino acid metabolism and hormone production to affect downstream defence-related gene expression via transcriptional regulation and nitric oxide (NO) production, which represents a direct link with N. Although the critical role of N nutrition in plant defences is stressed in this review, further work is urgently needed to provide a comprehensive understanding of how opposing virulence and defence mechanisms are influenced by interacting networks.